O estresse crônico de derrota social como modelo de depressão: envolvimento dos glicocorticoides - Nunes, Yasmin Cristina [UNIFESP] (2019)
Chronic exposure to social stress and hypothalamic-pituitary-adrenal axis (HPA) dysregulation are associated to depressive disorder. In this study we evaluated the effects of chronic exposure to social defeat stress on depressive-like behaviors and on HPA axis activity during and after the stress period. Moreover, we also evaluated if chronic social defeat could induce changes in glucocorticoids receptors (GR) levels and in its translocation in brain areas related to reward system and HPA axis regulation. For this purpose, male Swiss mice were exposed to social defeat stress during 10 days. In study 1, depressive-like behavior was assessed during sucrose splash test and social investigation test conducted 3 hours and 24 hours after the end of the stress protocol, respectively. In study 2, blood samples were collected 7 days before onset and during the social defeat protocol, as well as 24 hours after the last defeat for measurement of plasma corticosterone levels. In addition, 24 hours after the end of social defeat protocol the animals’ brains were collected for GR analysis in the hypothalamus, prefrontal cortex, ventral hippocampus and striatum. In study 3, the animals underwent social investigation test as an acute behavioral challenge and, 30 minutes later, blood samples were collected for measurement of plasma corticosterone levels. Our results show that defeated mice exhibited decrease in social interest with important individual differences, as well as a decrease in body grooming behaviour induced by sucrose solution. Plasma corticosterone levels during and after social defeat protocol were unchanged when compared to non-stressed animals. However, defeated animals showed an attenuated corticosterone response to an acute challenge when compared to control group. The brain GR levels and its translocation were unchanged in stressed animals when compared to control animals. These data suggest that chronic exposure to social defeat has a selective effect on some aspects related to depressive phenotype.